Evaluation of the oral and dental health of children with hemophilia in Turkey - Khlef, Mazen (My University, 2019)
Türkiye'deki Hemofilili Çocukların Ağız ve Diş Sağlığının Değerlendirilmesi.Mazen Khlef1, Prof. Dr. Şemsa İlknur Tanboğa11Marmara Üniversitesi, Diş Hekimliği Fakültesi, Pedodonti stanbul, Türkiye. Amaç: Bu çalışmanın amacı hemofili hastalığı olan çocuklarda diş çürüğü, plak ve dişeti iltihabı prevalansını değerlendirmektir.Gereç ve Yöntem: Hemofili A ve B tanılı 3-15 yaşları arasındaki 50 çocuğun ebeveynlerini, ağız sağlığı alışkanlıkları, ağız hijyeni ve ziyaret edilen dişhekiminin sıklığı, şeker tüketim sıklığı ve sosyoekonomik durumları hakkında sorular içeren bir anket yapıldı. Ek olarak, aşağıdakileri kaydetmek için intraoral muayene yapıldı: süt dişlerinde dmft, kalıcı dişlerde DMFT, modifiye gingival indeksi ve basitleştirilmiş oral hijyen indeksi. İstatistiksel değerlendirmede ortalama, standart sapma (SD), ortanca, sıklık, yüzde ölçümleri kullanıldı. Farklılıklar için Mann Whitney U testi ve Chi-Square testi kullanıldı. Anlamlılık seviyesi p <0.05 olarak ayarlandı.Bulgular: İstatistiksel olarak DMFT skoru, Gingival Index skoru, şeker tüketimi, anne ve baba eğitim durumu açısından anlamlı fark bulundu. Bununla birlikte, dmft, OHI-S skoru, fırçalama sıklığı ve önceki diş muayenesinde istatistiksel olarak anlamlı bir fark bulunmadı.Sonuç: Sonuçlar hemofilik çocuklar ağız sağlığının sağlıklılara neredeyse eşit olduğunu ortaya koydu. Aslında, ebeveynler için çocuklarının ağız sağlığı hizmetlerinin önemi konusunda eğitime daha fazla destek verilmelidir.

Evaluation of Dental Health of Children with Hemophilia in Turkey.Mazen Khlef 1, Prof. Dr. Şemsa İlknur Tanboğa11Marmara University, Faculty of dentistry, Pediatric Department, Istanbul, Turkey.Aim: The aim of this study is to evaluate the prevalence of dental caries, plaque, and gingivitis in children having hemophilia.Materials and Methods: Parents of 50 children, between 3 – 15 years old diagnosed with Hemophilia A and B, were surveyed using a questionnaire which includes questions about the oral health habits, the oral hygiene and the frequency of visiting dentist, the frequency of sugar consuming and their socioeconomic status. In addition, intraoral examination was performed to record the followings: dmft in the primary dentition, DMFT in the permanent dentition, modified gingival index and simplified oral hygiene index. The measures of mean, standard deviation (SD), median, frequency, percent were used for descriptive statistics. Mann Whitney U test and Chi-Square test were used for the differences. The significance level was set at p<0.05.Results: Statistically significant differences were found in DMFT score, Modified Gingival Index score, sugar consumption, maternal and paternal educational status. However, there was no statistically significant differences found in dmft, OHI-S score, brushing frequency and previous dental visit.Conclusion: The results revealed that the oral health of hemophilic children was nearly equal to the healthy ones. In fact, there should be more support on education for the parents about importance of oral health care of their children.
Keywords: children; Çocuk Diş Hekimliği; çocuklar : hemophilia; Dental care for children; Diş bakımı, Çocuklarda; DMFT; hemofili; Hemofili A; Hemophilia A; oral hijyen; oral hygiene; Pediatric Dentistry; Turkey; Türkiye